Stigma towards mental illness: A hospital-based cross-sectional study among caregivers in West Bengal - Shrabani Mukherjee; Dipta Kanti Mukhopadhyay (Wolters Kluwer Medknow Publications, 2018)
Background: Stigma among caregivers of people with mental illness has a serious impact on the disease outcome and lives of people with mental illness as well as other family members. Objectives: The objectives of this study were (i) To determine the level of self-perceived stigma toward mental illness, (ii) To measure perception to it among caregivers of people with mental illness, and (iii) To identify the factors associated with self-perceived stigma of caregivers. Methods: In this cross-sectional study, a structured interview was conducted among 200 caregivers of people with mental illness in the psychiatry outpatient department of a tertiary care hospital in West Bengal, India. Stigma and perception regarding mental illness were assessed with a validated 12-item Explanatory Model Interview Catalogue and 20-item perception scale, respectively. Information on their sociodemographic characteristics was also collected. Results: Average stigma score (53.3 ± 13.2) was higher than 50% of maximum attainable score. Caregivers of higher age, female gender, low income, higher education, manual job, rural residence, and those who are single or widowed scored higher in stigma scale. Caregivers with female gender (P = 0.007) and rural residence (P = 0.01) were more likely to have stigma while the perception score was negatively associated (P < 0.001) with stigma score. Conclusion: The study highlighted that health-care providers can play a pivotal role to address caregivers' stigma in order to alleviate its effect on the course of illness and improve family life.